PENGGUNAAN MODEL KOOPERATIF SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA KELAS XI MATA PELAJARAN PKN - yarso, Aswandi; Aminuyati, Aminuyati; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to 1) find out the learning outcomes before using the snowball throwing learning model. 2) find out the learning outcomes after using the snowball throwing learning model. 3) find out the differences before and after using the snowball throwing learning model. The method in this study was an experiment with pre-experimental one-group pretest-posttest design. The population in this study was class XI MA Raudatul Ulum Meranti in Academic Year 2018/2019 with 32 male students as the samples. Sampling was carried out by a purposive technique. The research instrument used was 15 pretest and posttest questions. Data analysis techniques in this study were descriptive statistical data analysis and effect size test. Based on descriptive analysis obtained data on learning outcomes of students namely the average pretest score was 49.68 while the posttest was 76.18 occured an increase with a difference in value of 26.50 was 53.34%.based on the effect size test that is 1.94 with a high category. It can be concluded that, there is an increase in student learning outcomes when the use of snowball throwing learning models means that Ho is rejected. If Ho is rejected, Ha is accepted, which means there are differences in the learning outcomes of grade XI students, MA MA Raudatul Ulum Meranti.Â Keywords: Snowball throwing implementation, Civics Learning Outcomes